A framework implementation of surveillance tracking system based on PIR motion sensors - Bashar Alathari; Mohammed Falih Kadhim; Salam Al-Khammasi; Nabeel Salih Ali (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
A motion tracking system made from affordable hardware components is implemented to be used inside the University of Kufa (UoK) buildings to track and detect any suspicious activities. The current research objectives are to automatically monitor, track intruders using sensors, servo, and camera that occurs around the system using Arduino microcontroller. The mounted camera track, capture the moving object and sending a live broadcast to a receiving host which could be a desktop computer, laptop, tablet or a smartphone. In this study, we consider the problem of automated position estimation using the electronic circuit of inexpensive binary motion sensors. We present simulation and experiments with Passive Infrared (PIR) motion sensors that suggest our current estimator. Fritzing software simulator is used to test and draw the circuits of the system. The proposed design worked efficiently during the experiments and shown high performance with 360 degrees of detection for the sensing environments.